2017
DOI: 10.14260/jemds/2017/219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antenatal Lactation Counselling and Postnatal Lactation Support in Improving Breastfeeding Initiation Rates and Exclusive Breastfeeding in Less Educated Mothers of Rural Area of Chandu- Budhera

Abstract: BACKGROUND Human breast milk is the best source of nourishment for the human infants. Breastfeeding promotes health and helps to prevent disease. Antenatal lactation counselling and postnatal lactation support have an impact in initiation of breastfeeding immediately after birth and in practicing exclusive breastfeeding for first 6 months of infant's life. The objective of this study is to study the impact of antenatal lactation counselling and postnatal lactation support to mothers of newborns in improving br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The successful modes of delivery by health professionals were regularly monitored antenatal care in health facilities, predesigned nutrition education by nutritionist, and additional sessions that were inserted in frequent meetings for microcredit female recipients. In one hand, antenatal education was suggested as a promising intervention for mothers with low educational level (Kapur et al, 2017), particularly in empowering mothers to access antenatal care services and better prepare baby delivery (Ananthakrishnan et al, 2012;Ingram, MacArthur, Khan, Deeks, & Jolly, 2010;Kawaguchi et al, 2014). In a longer term, a regular antenatal care visit positively correlated with exclusive breastfeeding practice (Tariku et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The successful modes of delivery by health professionals were regularly monitored antenatal care in health facilities, predesigned nutrition education by nutritionist, and additional sessions that were inserted in frequent meetings for microcredit female recipients. In one hand, antenatal education was suggested as a promising intervention for mothers with low educational level (Kapur et al, 2017), particularly in empowering mothers to access antenatal care services and better prepare baby delivery (Ananthakrishnan et al, 2012;Ingram, MacArthur, Khan, Deeks, & Jolly, 2010;Kawaguchi et al, 2014). In a longer term, a regular antenatal care visit positively correlated with exclusive breastfeeding practice (Tariku et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…2011). Meanwhile, one study was a non-RCT (Kapur, Yamini Gupta, & Kumar, 2017). Our review identified two cohort studies recalling mothers' experience on the time of breastfeeding initiation and evaluating the factors associated with the EIBF practice (Khanal, Scott, Lee, Karkee, & Binns, 2015;Patel et al, 2015).…”
Section: Methods Used By Studiesmentioning
confidence: 99%
See 3 more Smart Citations